Inefficiency in the Shadow of Unobservable Outside Options - ANEY, Madhav S. (Institutional Knowledge at Singapore Management University, 2012)
This paper considers the problem of allocating an object between two players in an environment with one sided asymmetric information when their outside options depend on each other's type, causing the outside option of the uninformed player to be unobservable to her. Consequently efficient mechanisms under budget balance are not always available even when there is no uncertainty about which of the two players values the object more. A simple condition on the outside options turns out to be both necessary and sufficient to guarantee the first best. I also characterise the second best allocation under some conditions and show how it varies with changes in the outside options. I argue that the model applies to an environment where property rights over the object are not well defined and their enforcement is subject to an inefficient default game such as a contest. In such cases type dependent outside options arise naturally as the equilibrium payoffs from the default game. The model can explain why the best ways of avoiding inefficient default games, such as arbitration as a way of avoiding litigation, typically involve a degree of inefficiency.